Effect of simulated obstructive hypopnea and apnea on thoracic aortic wall transmural pressures. - Clarenbach, C; Camen, G; Sievi, N; Wyss, C; Stradling, JR; Kohler, M (2013)
Preliminary evidence supports an association between obstructive sleep apnea (OSA) and thoracic aortic dilatation, although potential causative mechanisms are incompletely understood; these may include an increase in aortic wall transmural pressures, induced by obstructive apneas and hypopneas. In patients undergoing cardiac catheterization, mean blood pressure (MBP) in the thoracic aorta and esophageal pressure was simultaneously recorded by an indwelling aortic pigtail catheter and a balloon-tipped esophageal catheter in randomized order during: normal breathing, simulated obstructive hypopnea (inspiration through a threshold load), simulated obstructive apnea (Mueller maneuver), and end-expiratory central apnea. Aortic transmural pressure (aortic MBP minus esophageal pressure) was calculated. Ten patients with a median age (range) of 64 (46-75) yr were studied. Inspiration through a threshold load, Mueller maneuver, and end-expiratory central apnea was successfully performed and recorded in 10, 7, and 9 patients, respectively. The difference between aortic MBP and esophageal pressure (and thus the extra aortic dilatory force) was median (quartiles) +9.3 (5.4, 18.6) mmHg, P = 0.02 during inspiration through a threshold load, +16.3 (12.8, 19.4) mmHg, P = 0.02 during the Mueller maneuver, and +0.4 (-4.5, 4.8) mmHg, P = 0.80 during end-expiratory central apnea. Simulated obstructive apnea and hypopnea increase aortic wall dilatory transmural pressures because intra-aortic pressures fall less than esophageal pressures. Thus OSA may mechanically promote thoracic aortic dilatation and should be further investigated as a risk factor for the development or accelerated progression of thoracic aortic aneurysms.